ECOLOGY AND MANAGEMENT OF AN ESTUARY AT THE EDGE OF THE AMERICAN CARIBBEAN: BISCAYNE BAY - Thorhaug, Anitra (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Biscayne Bay is a shallow subtropical estuary, 225 square miles of water, at the edge of the tropics, located within Dade County, one of the fastest growing counties in the U.S.A. The fragility of this seagrass and mangrove dominated estuary has been demonstrated by repeated destruction of these ecosystems by man's activities, such as dredging, filling, drainage, sewerage, thermal pollution, and others. At the southern end, the U.S. Department of the Interior has recently established the Biscayne Monument, a preserve area where fairly rigit restrictions for man's use of the biota are enforced. At the northern end, intense land development since 1910 along with establishment for artificial islands and causeways, bulkheading, sewerage outfall and other pollutants has altered the ecology greatly. Approximately 1.5 million people inhabit this area. Multiple authorities for regulating use in the bay and its shoreline exist ranging from county to Federal. Many problems of overlapping jurisdiction and enforcement occur. Two symposia to bring together the knowledge of processes occurring m the bay and to delineate a policy for managing the bay were held in March 1976 resulting in the Volume, Biscayne Bay: Past, Present, and Future. Aspects of the ecology of this bay and of the management problems and goals will be discussed.